KINETIC AND THERMODYNAMIC STUDIES OF METHYL ORANGE ADSORPTION ONTO MESOPOROUS CARBON COATED MONOLITH (SYNTHESIZED BY SURFACTANT) - M.I.M, Zamratul,; S.Y. Choong, Thomas, (Malaysian Journal of Science, 2013)
Ceramic monolith was chemically modified for the purpose of developing an adsorbent known as carbon coated monolith (CCM). The carbon coated monolith was characterized by using Brunauer-Emmet and Teller (BET) and Barret-Joyner-Halenda (BJH), point zero charge (pHpzc) and surface chemistry. The kinetics adsorption of methyl orange followed a pseudo-second order kinetic model. Thermodynamic parameters such as enthalpy change (∆H°), free energy change (∆S°) and entropy change (∆G°) were calculated from the slope and intercept of the linear plot of ln KL against 1/T. Analysis of adsorption results obtained at T= (298 K, 303 K and 313 K) showed that the adsorption process of methyl orange was found to be endothermic and spontaneous. ABSTRAK Monolit seramik telah dimodifikasi secara kimia untuk digunakan sebagai penjerap yang dikenali sebagai monolit mesopori bersalut karbon. Monolit mesopori bersalut karbon telah diujikaji melalui analisa Brunauer-Emmet and Teller (BET) dan Barret-Joyner-Halenda (BJH), titik caj sifar (pHpzc) dan kimia permukaan. Data kinetik bagi jerapan menunjukkkan bahawa jerapan mematuhi model kadar tertib pseudo-kedua. Ujikaji parameter termodinamik seperti entalpi ∆H°, perubahan entropi ∆S° dan perubahan tenaga bebas ∆G° telah diukur dari kecerunan dan pintasan yang diperolehi dari plot ln KL melawan 1/T. Analisa menunjukkan proses penjerapan adalah bersifat endotermik dan spontan (Keywords: Adsorption, methyl orange, mesoporous monolith, kinetic, thermodynamic. )